Legal Policies in Protecting Victims of Online Gender-Based Violence: A Victimology Perspective - I Putu Edi Rusmana; Made Sinthia Sukmayanti (KRTHA BHAYANGKARA, 2026)
This study examines criminal law policies in protecting and recovering victims of Online Gender-Based Violence (OGBV) within the Indonesian criminal justice system from a victimology perspective. Although several legal instruments, such as Law Number 12 of 2022 concerning Sexual Violence Crimes and Law Number 19 of 2016 concerning Electronic Information and Transactions, provide a normative basis for addressing OGBV, their implementation has not yet ensured effective protection and recovery for victims. This research employs normative legal research using statutory, conceptual, and comparative approaches to evaluate existing legal frameworks and assess their effectiveness in preventing secondary victimization. The findings reveal that the Indonesian criminal justice system remains predominantly offender-oriented, resulting in limited access to victim recovery services, weak institutional coordination, and the absence of an effective compensation mechanism. These structural weaknesses contribute to the persistence of secondary victimization experienced by OGBV victims. Based on these findings, this study proposes a victim-centered criminal law policy model that integrates victim recovery mechanisms, compensation schemes, capacity building for law enforcement officers, and stronger collaboration with digital platforms in handling OGBV cases. The study contributes to the development of criminal law policy by offering a victimology-based framework for the protection and recovery of OGBV victims, which may serve as an academic reference for strengthening victim-oriented approaches within Indonesia’s cybercrime and gender-based violence policies.